Mudanças institucionais - Olinger, Glauco (2025)
Reorganization is the first thought that arises among managers, administrators and consultants, especially in the public sector, when the need to improve the performance of institutions is felt. At the time when one seeks to reformulate Epagri, it seems convenient to consider the experiences lived by other nations that have faced and are facing similar problems, in addition to qualified consultants, such as José de Souza, who have the necessary knowledge to avoid becoming part of that unacceptable statistic.